IMPROVING STUDENTS’ READING COMPREHENSION THROUGH STORY GRAMMAR STRATEGY - Herawati, Herawati (Lentera: Jurnal Ilmiah Kependidikan, 2018)
Reading comprehension is a bridge to understand scientific books that is why the students of Indonesia should to understand and comprehend. The study aims to know whether story grammar strategy improve the students’ reading comprehension or not. The focus of this study was the tenth grades students of SMA Negeri Bangun Jaya, X1 as experiment group and X3 as control group. The sample was chosen by the cluster sampling technique. This study was non-equivalent control group design. The data was analyzed by using pretest and posttest data. The result showed there was significant difference in reading comprehension achievement between the students who were taught by using story grammar strategy and those who were taught by using conventional strategy. The students who are taught by using story grammar strategy could improve their reading comprehension achievement significantly. Most of the students in the experimental group could share the information of the next to their classmates.